PROSPECTS OF NEUROMORPHIC TECHNOLOGIES AND ARTIFICIAL INTELLIGENCE IN THE EDUCATIONAL PROCESS (Web of Teachers: Inderscience Research, 2023)
This article discusses the possibilities of both artificial intelligence and neuromorphic technologies that should be used in the educational process to improve the skills and competencies of students in the educational process.